Pseudomonas aeruginosa N-3-oxo-dodecanoyl-homoserine Lactone Elicits Changes in Cell Volume, Morphology, and AQP9 Characteristics in Macrophages - Holm, Angelika; Magnusson, Karl-Eric; Vikström, Elena (Frontiers in Cellular and Infection Microbiology, 2016)
Quorum sensing (QS) communication allows P. aeruginosa to collectively control its population density and the production of biofilms and virulence factors. QS signal molecules, like N-3-oxo-dodecanoyl-L-homoserine lactone (3O-C12-HSL), can also affect the behavior of host cells, e.g. by modulating the chemotaxis, migration and phagocytosis of human leukocytes. Moreover, host water homeostasis and water channels aquaporins (AQP) are critical for cell morphology and functions as AQP interact indirectly with the cell cytoskeleton and signaling cascades. Here, we investigated how P. aeruginosa 3O-C12-HSL affects cell morphology, area, volume and AQP9 expression and distribution in human primary macrophages, using quantitative PCR, immunoblotting, two- and three-dimensional live imaging, confocal and nanoscale imaging. Thus, 3O-C12-HSL enhanced cell volume and area and induced cell shape and protrusion fluctuations in macrophages, processes tentatively driven by fluxes of water across cell membrane through AQP9, the predominant AQP in macrophages. Moreover, 3O-C12-HSL upregulated the expression of AQP9 at both the protein and mRNA levels. This was accompanied with enhanced whole cell AQP9 fluorescent intensity and redistribution of AQP9 to the leading and trailing regions, in parallel with increased cell area in the macrophages. Finally, nanoscopy imaging provided details on AQP9 dynamics and architecture within the lamellipodial area of 3O-C12-HSL-stimulated cells. We suggest that these novel events in the interaction between P. aeruginosa and macrophage may have an impact on the effectiveness of innate immune cells to fight bacteria, and thereby resolve the early stages of infections and inflammations.